2012
DOI: 10.2147/ijn.s28098
|View full text |Cite
|
Sign up to set email alerts
|

Cell responses to two kinds of nanohydroxyapatite with different sizes and crystallinities

Abstract: Introduction:Hydroxyapatite (HA) is the principal inorganic constituent of human bone. Due to its good biocompatibility and osteoconductivity, all kinds of HA particles were prepared by different methods. Numerous reports demonstrated that the properties of HA affected its biological effects. Methods: Two kinds of nanohydroxyapatite with different sizes and crystallinities were obtained via a hydrothermal treatment method under different temperatures. It was found that at a temperature of 140°C, a rod-like cry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
41
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(49 citation statements)
references
References 31 publications
6
41
0
Order By: Relevance
“…The idea that different NP shapes may differentially influence cell behaviour has been measured using apoptosis and proliferation assays [15], as well as protein expression analysis [16] and stains for NP uptake in a macrophage cell line [16 -19]. An experiment testing two differently sized rod-shaped HA NPs on an osteoblast-like (osteosarcoma) cell line found that although the smaller particles caused a significant amount of cells to apoptose, there was no difference in alkaline phosphatase activity [20]. Another study found that rod-shaped particles caused primary osteoblasts to decrease their proliferation after 3 days of culture compared with spherical-shaped.…”
Section: Introductionmentioning
confidence: 99%
“…The idea that different NP shapes may differentially influence cell behaviour has been measured using apoptosis and proliferation assays [15], as well as protein expression analysis [16] and stains for NP uptake in a macrophage cell line [16 -19]. An experiment testing two differently sized rod-shaped HA NPs on an osteoblast-like (osteosarcoma) cell line found that although the smaller particles caused a significant amount of cells to apoptose, there was no difference in alkaline phosphatase activity [20]. Another study found that rod-shaped particles caused primary osteoblasts to decrease their proliferation after 3 days of culture compared with spherical-shaped.…”
Section: Introductionmentioning
confidence: 99%
“…Again, similar cell morphologies and good cell viability were observed; however, it was concluded that high surface area could increase cell-particle interaction [739]. Nevertheless, another study with cellular response to rod-shaped HA bioceramics, revealed that some types of crystals might trigger a severe inflammatory response [742]. In addition, CaPO 4 -based sealers appeared to…”
Section: Cellular Responsementioning
confidence: 94%
“…MG‐63 osteoblasts were seeded in each scaffold with 1 × 10 6 cells and maintained in an alpha‐MEM medium (α‐MEM: Gibco ® , Invitrogen™, Carlsbad, CA) with the addition of 1% penicillin/streptomycin, 0.1% Fungizone, and 10% fetal bovine serum at 37°C in a humidified 5% CO 2 /95% air incubator. The medium was changed every 3–4 days . An osteogenic medium (OS: 20 m M b ‐glycerophosphate, 50 µ M ascorbic acid, and 100 n M dexamethasone; Sigma‐Aldrich) was used for osteoblast differentiation of the MG‐63 osteoblast cells …”
Section: Methodsmentioning
confidence: 99%